Measurement of the lower canine pulp chamber through periapical radiography for age estimation - Otty Ratna Wahyuni; Deny Saputra; Nastiti Faradilla Ramadhani; Dennaya Listya Dias (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: The principle of measurement using the TCI (Tooth Coronal Index) method is to compare the pulp chamber height with a person's chronological age based on the formation of secondary dentin. The purpose of this study is to estimate age based on pulp chamber height in lower canines using periapical radiographs with TCI measurement. Materials and Methods: This study is an observational analytic study using 42 samples of periapical radiographs with the parallel technique of the lower canines. Samples were measured for CH and CPCH heights to determine TCI values and then linear regression was made to determine their biological age. Finally, the difference between biological and chronological age is calculated to determine the approximate age. Results: The mean difference between chronological age and biological age was ± 5.05 years and an average biological age of 29.38 years. Conclusion: TCI method based on pulp chamber height in lower canines using periapical radiographs can be used to estimate age with the difference between chronological age and biological age of ±5.05 years.